Scores, Camera, Action : Social Accountability and Teacher Incentives in Remote Areas - Gaduh, Arya; Pradhan, Menno; Priebe, Jan; Susanti, Dewi (World Bank, Washington, DC, 2021)
Remote schools in developing countries are costly to supervise, resulting in low teacher accountability and poor education outcomes. This paper reports the results of a randomized evaluation of three treatments that introduced teacher incentives based on community monitoring of teacher effort against locally agreed standards. The Social Accountability Mechanism (SAM) treatment facilitated a joint commitment between schools and community members to improve learning. Teacher performance was rated against it, discussed in monthly public meetings and passed on to authorities. The second and third treatments combined SAM with a performance pay mechanism that would penalize eligible teachers’ remote area allowance for poor performance. In the SAM+Camera (SAM+Cam) treatment, the cut was based on absence as recorded by a tamper-proof camera; while in the SAM+Score treatment, it was based on the overall rating. After one year, the findings indicate improvements in learning outcomes across all treatments; however, the strongest impact of 0.20 standard deviation is observed for SAM+Cam. The evaluation also finds a small positive impact on the effort of affected teachers for SAM+Cam and SAM, and significant positive improvements on parental educational investments in all treatments. For SAM and SAM+Cam, additional data were collected in the second year (one year after project facilitators left). The findings show that SAM+Cam’s impacts on learning outcomes and parental investments—but not teacher effort —persisted into the second year.